A comprehensive view of adolescent sexual health and family planning from the perspective of Black and Hispanic adolescent mothers in New York city - Lauren Gerchow; Yzette Lanier; Anne-Laure Fayard; Allison Squires (SSM: Qualitative Research in Health)
Black and Hispanic adolescents in New York City experience high rates of pregnancy and sexually transmitted infections. A comprehensive understanding of the complexity of adolescent sexual health and family planning decisions and experiences can provide insights into the sustained disparities and inform practice, policy, and future research. The goal of this study was to explore and analyze this complexity, centering Black and Hispanic adolescent mothers as the experts on sexual and reproductive experiences from pre-pregnancy through parenting. As part of formative research for a human-centered design study, we interviewed 16 Black and Hispanic adolescent mothers living in New York City. Using situational analysis, we mapped relationships, discourse, and social structures to explore the various factors that inform adolescent sexual health decisions, in particular choices about contraception. Situational analysis found that, besides interpersonal factors, organizations and non-human elements like social media and physical birth control devices affected adolescent family planning in three social arenas: home, healthcare, and school. Within and across these arenas, adolescents lacked consistent sexual health education and contraceptive counseling and faced gendered expectations of their behaviors. Participants described parents and healthcare providers as most responsible for providing sexual health counseling yet described parents as uncomfortable or overreactive and healthcare workers as paternalistic and biased. A consideration of the many factors that inform sexual health decision-making and recognition of adolescents’ desire for parents and healthcare providers to be a source of education can address health disparities and promote adolescent sexual health and wellbeing.